Frontiers of peace economics and peace science - Chatterji, Manas, 1937-; Bo, Chen.; Misra, R. P. (Rameshwar Prasad), 1930- (Bingley, U.K. : Emerald, 2011)
Over the last three decades, a considerable amount of work has been conducted in the field of peace studies, conflict management, peace science in economics, sociology, anthropology and management. This volume presents up-to-date, cutting-edge research by respected scholars with an emphasis on theoretical and mathematical constructs in the area of peace economics & peace science.
Armed confrontations, irrevocable decisions, and stability in conflict / Urs Luterbacher -- Analytic narratives, game theory, and peace science / Frank C. Zagare -- International and domestic uncertainties in the traditional deterrence game / Lisa J. Carlson, Raymond Dacey -- When costs approach infinity : microeconomic theory, security, and dangerous technologies / Lloyd J. Dumas -- The costs of conflict : UK experience in Afghanistan and Iraq / Keith Hartley -- Economists' controversies about the causality between war and economic cycles / Fanny Coulomb, Liliane Bensahel-Perrin, Jacques Fontanel -- Beyond the battlefield : wars without soldiers / Sheldon G. Levy -- Military spending and economic growth in China, 1953-2007 : a note on econometric analysis by using eviews / Chen Bo, Xing Xing -- New challenges and'old business with Russia' : a revival of an idea of'competitive coexistence' / Vladimir Rukavishnikov -- Economic foundation of conflicts in the Middle East / Nasser Elkanj, Partha Gangopadhyay --'We're losing the fight against nuclear proliferation' / Michael D. Intriligator -- Water conflict management issues : the Middle East / Saul Arlosoroff.
Includes indexes.
Keywords: Peace -- Economic aspects; Peace-building -- Economic aspects